Impact of comorbidity on patients with COVID-19 in India: A nationwide analysis - Singh, Priya; Bhaskar, Yogendra; Verma, Pulkit; Rana, Shweta; Goel, Prabudh; Kumar, Sujeet; Gouda, Krushna Chandra; Singh, Harpreet (Frontiers in Public Health, 2023)
ABSTRACT: Background: The emergence of COVID-19 witnessed global pandemic resulting huge loss of life and negative change on world economic loss world over. There is a need to understand the COVID-19 disease dynamics in a clustered way for a large country like India. Objective: To evaluate the clinical characteristics of COVID-19 patients based on age, gender and pre-existing comorbidities. The patients are being classified as per the comorbidities and their impact on the severe outcomes of COVID-19 are analysed by considering the data for the period of about 2 years i.e., 1 January 2020 to 31 January 2022. Methods: The distribution of COVID-19 positive, hospitalised and death cases was estimated for different age/gender groups. The impact of comorbidities are assessed by computing the Incidence rate (IR), odd ratio (OR) and proportion analysis. Results: The results indicated an exponential growth in mortality due to COVID-19. In the case of patients above the age 50 years, the death was found to be very high with about 80%. Moreover, the odd ratio estimation inferred that the age and various pre-existing comorbidities were found to be the predictor of severe COVID-19 outcomes. The strongest risk factors for death due to COVID-19 were the patients with pre-existing comorbidities like Diabetes (OR 2.39; 95% CI: 2.31- 2.47; p<0.0001), Hypertension (OR 2.31; 95% CI:2.23-2.39; p<0.0001) and Heart Diseases (OR 2.19; 95% CI: 2.08-2.30; P<0.0001). The proportion of fatal cases among the Covid-19 positive patients increased with the number of comorbidities. Conclusion: The study inferred that the elderly patients with pre-existing comorbidities are at higher risk of mortality due to COVID-19. The elderly age-group patients with underlying medical conditions are recommended for the pre-cautionary healthcare or medical resources and vaccination against COVID-19. Keywords: COVID-19, Comorbidity, Odd Ratio, Epidemiology.